Studies on Platinum(II) and Palladium(II) Complexes of Some Substituted Pyrazole-5-ones, Pyrazoles, Arylhydroxy Pyrazoles and Pyrano Pyrazoles - A.K. Al-Allaf , Talal; I.H. Al-Bayati, Redha (Asian Journal of Chemistry, 2010)
The coordination behaviour of several pyrazole-5-ones and pyrazoles derivatives with platinum(II) and palladium(II) metals have been reported by the isolation and characterization of the resulting complexes. These complexes possess a square planer structures (cis-form) as revealed from IR and NMR spectml data. The ligands were coordinated mainly through the N—N linkage of the pyrazole ring.